Behavioural Intention of Millennial Generation FinTech Users: Does Self-Efficacy Influence Digital Technostress and Social Influence? - Amelia Dwi Wahyuni; Zaki Baridwan; Syaiful Iqbal (AFRE (Accounting and Financial Review), 2024)
This study aims to provide empirical evidence on the influence of technostress and social influence on the intention to use fintech. Additionally, this study offers empirical evidence on the ability of self-efficacy to moderate the impact of technostress and social influence on the intention to use fintech. The sample for this study was selected using purposive sampling and comprised 404 respon-dents who are millennial fintech users and work as private employees in Sa-marinda City. This study employs a quantitative research design, with primary data obtained directly from respondents through questionnaires. The data ana-lysis method used in this research is Partial Least Square (PLS). The results in-dicate that technostress, consisting of techno-overload, techno-invasion, and techno-complexity, negatively affects the intention to use fintech. Furthermore, social influence positively affects the intention to use fintech. However, techno-uncertainty does not impact the intention to use fintech. This study finds that self-efficacy can mitigate the negative impact of techno-overload on the inten-tion to use fintech. Similarly, social influence is also moderated by self-efficacy, thereby increasing the intention to use fintech. However, self-efficacy does not reduce the negative effects of techno-overload, techno-invasion, and techno-un-certainty on the intention to use fintech among millennials.DOI: https://doi.org/10.26905/afr.v7i2.13534. Â